Surgical treatment of rostrotentorial meningioma complicated by foraminal herniation in the cat. Issue 12 (December 2020) - Kouno, Shigenori; Shimada, Masakazu; Sato, Asaka; Kanno, Nobuo; Suzuki, Shuji; Harada, Yasuji; Hasegawa, Daisuke; Hara, Yasushi
Objectives: This study was performed to evaluate retrospectively the clinical signs, complications and postoperative outcomes of feline intracranial meningioma (IM) with concurrent cingulate, transtentorial and foramen magnum herniations. Methods: The medical records and MRI scans of cats with IM and cerebral herniation were reviewed. Cases involving concurrent cingulate, transtentorial and foramen magnum herniations were included. Owners were contacted to obtain long-term follow-up information. Results: Seven cats (four castrated males and three spayed females) met the inclusion criteria. Median age was 13.0 years (range 9.9–16.1 years) and median duration of clinical signs was 35 days (range 21–163 days). The clinical signs of cats with cerebral herniation included visual impairment (n = 5 [71.4%]), ataxia (n = 4 [57.1%]), impaired consciousness (n = 2 [28.6%]), head pressing (n = 2 [28.6%]), paresis (n = 1 [14.3%]), torticollis (n = 1 [14.3%]) and personality changes (n = 1 [14.3%]). Median tumour volume, cranial cavity volume and tumour volume:intracranial volume ratio before surgery were 3.37 cm 3 (range 3.23–11.5 cm 3 ), 32.6 cm 3 (range 29.8–78.3 cm 3 ) and 10.4% (range 5.3–35.3%), respectively. Median overall tumour excision rate was 90.6%. Preoperative intracranial pressure (ICP) ranged from 15 to 32 mmHg (median 29 mmHg). In all cases, the ICP dropped to 0 mmHg immediately after tumour removal. No adjuvant therapy was required after surgery. The median survival period was 612 days (range 55–1453 days). Conclusions and relevance: The results of this study indicate that surgical treatment of rostrotentorial IM is effective and allows prolonged survival, even in cats with concurrent cingulate, transtentorial and foramen magnum herniations.